2021
DOI: 10.1080/0886022x.2021.1896548
|View full text |Cite
|
Sign up to set email alerts
|

The role of discoidin domain receptor 2 in the renal dysfunction of alport syndrome mouse model

Abstract: Alport syndrome (AS) is a hereditary glomerular nephritis caused by mutation in one of the type IV collagen genes α3/α4/α5 that encode the heterotrimer COL4A3/4/5. Failure to form a heterotrimer due to mutation leads to the dysfunction of the glomerular basement membrane, and end-stage renal disease. Previous reports have suggested the involvement of the receptor tyrosine kinase discoidin domain receptor (DDR) 1 in the progression of AS pathology. However, due to the similarity between DDR1 and DDR2, the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…In the UUO model, downregulation of DDR1 expression with AON 2 days after injury reduced inflammation and preserved renal structure ( Kerroch et al, 2016 ). In contrast to this finding, downregulation of DDR2 expression with AON in a mouse model of Alport syndrome did not decrease proteinuria, inflammation or fibrosis ( Sannomiya et al, 2021 ), despite lowering the levels of MCP-1 and collagen I. It is not clear whether lack of overall beneficial effects are due to incomplete depletion of DDR2 or whether DDR2 does not play a role in the kidney injury in this animal model.…”
Section: Pharmacological Approaches For Targeting Discoidin Domain Re...contrasting
confidence: 72%
See 2 more Smart Citations
“…In the UUO model, downregulation of DDR1 expression with AON 2 days after injury reduced inflammation and preserved renal structure ( Kerroch et al, 2016 ). In contrast to this finding, downregulation of DDR2 expression with AON in a mouse model of Alport syndrome did not decrease proteinuria, inflammation or fibrosis ( Sannomiya et al, 2021 ), despite lowering the levels of MCP-1 and collagen I. It is not clear whether lack of overall beneficial effects are due to incomplete depletion of DDR2 or whether DDR2 does not play a role in the kidney injury in this animal model.…”
Section: Pharmacological Approaches For Targeting Discoidin Domain Re...contrasting
confidence: 72%
“…In contrast to DDR1, whether and where DDR2 expression is upregulated in subjects with kidney disease has not been investigated. In some animal models of kidney injury like Alport syndrome ( Sannomiya et al, 2021 ) and UUO ( Li et al, 2019b ), upregulation of DDR2 expression has been shown by Western blot and RT-PCR, respectively. However, no changes in DDR2 expression are observed in the remnant kidney model ( Lee et al, 2004 ).…”
Section: Discoidin Domain Receptor Expression In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the main role of DDR1 and DDR2 in human cancer, they are also involved in other disorders such as inflammation, tissue fibrosis and atherosclerosis, and neurodegenerative diseases [ 5 , 90 , 91 , 92 ]. A study by Matsuyama et al, reported that DDR1 not only stimulated inflammatory factor secretion, but it also enhanced the effects of other stimuli including proinflammatory cytokines or bacterial products [ 93 ].…”
Section: Role Of Ddr In Inflammation and Neurodegenerative Disordersmentioning
confidence: 99%
“…The role of DDR2 (discoidin domain receptor 2), highly similar to DDR1, was investigated in an X-linked AS mouse (B6). DDR2, despite having high expression levels in AS, does not have a clear implication in the pathogenesis of AS [ 69 ].…”
Section: Molecular Basis Of the Diseasementioning
confidence: 99%